The construction of π_0 in Axiomatic Cohesion - Menni, Matías (2017)
We study a construction suggested by Lawvere to rationalize, within a generalization of Axiomatic Cohesion, the classical construction of 0 as the image of a natural map to a product of discrete spaces. A particular case of this construction produces, out of a local and hyperconnected geometric morphism p : E ! S, an idempotent monad pi_0 : E ightarrow E such that, for every X in E, pi_0 X = 1 if and only if (p^* Omega)^! : (p^* Omega)^1 ightarrow (p^* Omega)^X is an isomorphism. For instance, if E is the topological topos (over S = Set), the pi_0-algebras coincide with the totally separated (sequential) spaces. To illustrate the connection with classical topology we show that the pi_0-algebras in the category of compactly generated Hausdorff spaces are exactly the totally separated ones. Also, in order to relate the construction above with the axioms for Cohesion we prove that, for a local and hyperconnected p : E ightarrow S, p is pre-cohesive if and only if p^* : S ightarrow Eis cartesian closed. In this case, p_! = p_* pi_0 : E ightarrow S and the category of pi_0-algebras coincides with the subcategory p^* : S ightarrow E.